1990
DOI: 10.1152/ajprenal.1990.258.6.f1675
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of salt restriction over diuretics in reducing renal hypertrophy and injury in uninephrectomized SHR

Abstract: Spontaneously hypertensive rats (SHR) were uninephrectomized (UNX) at 6 wk of age and given either standard chow (CON), low-sodium chow (LSC), or standard chow and hydrochlorothiazide (HCTZ) added to the drinking water. Severe hypertension developed in all three groups. Forty-two weeks after UNX, proteinuria and glomerular sclerosis were significantly lower in LSC than in CON or HCTZ. The protective effect of salt restriction did not depend upon alterations in plasma renin concentration or glomerular hemodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…Similar prevention of proteinuria by dietary sodium restriction was previously described in uninephrectomized spontaneously hypertensive rats (3) and 5/6 nephrectomy model (10). In the latter studies (3,10), it was clearly shown that reduction in glomerular pressure determined by micropuncture or arterial pressure did not account for the beneficial effect of sodium restriction.…”
Section: Discussionmentioning
confidence: 97%
“…Similar prevention of proteinuria by dietary sodium restriction was previously described in uninephrectomized spontaneously hypertensive rats (3) and 5/6 nephrectomy model (10). In the latter studies (3,10), it was clearly shown that reduction in glomerular pressure determined by micropuncture or arterial pressure did not account for the beneficial effect of sodium restriction.…”
Section: Discussionmentioning
confidence: 97%
“…Dietary salt intake plays an important role not only in blood pressure but also in the progression of glomerular injury (20)(21)(22). Dahl-S rats are the most popular model of human salt-sensitive hypertension (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the uninephrectomised SHR salt restriction inhibits compensatory kidney growth. 59 In patients with hypertension an increase in salt intake often increases glomerular filtration rate, vascular resistance, calculated intraglomerular capillary pressure and protein excretion. 60 In normal humans the effect of a raised salt intake varies from no detectable effect or a decrease in renal vascular resistance, a few have a similar response to that which occurs in those hypertensive patients who have an increase in glomerular filtration.…”
Section: Renal Functionmentioning
confidence: 99%